Effect of temperature and rigor of aeration on the efficiency of wastewater treatment from a car wash in bioreactors with a moving bed (MBBR) - Włodyka-Bergier, Agnieszka; Kowalewski, Zbigniew; Mazur , Robert (Instal, 2023)
Biological methods are an indispensable part of municipal wastewater treatment. Under high volume of wastewater and high concentrations of COD and nutrients, these methods are the optimal technology. The article presents an attempt application of biological methods to treat wastewater from a car wash. This wastewater is characterized by content of detergents and carbon compounds and high flow irregularity. It used activated sludge sequencing batch reactors (SBR) and moving bed reactors (MBBR) using three types of carriers: Mutag BioChip 30™, BioFLO 9 and Hel-X (H2X36 35/36). The volume of the reactors was 20 dm3, the total operating time was 20 hours. A set of physicochemical parameters were determined in the wastewater, however, the main analyses focused on: COD, BOD5, color, turbidity and biogens – nitrogen and phosphorus. The study showed the high capacity of the reactors’ biocenosis to reduce pollutant concentrations. Biogenes and COD are removed with 60% efficiency, BOD5 with 80%, and color and turbidity at more than 90%.